P389 Systematic review and meta-analysis of risk factors for recurrent primary sclerosing cholangitis. (25th January 2019) - Steenstraten, I; Sebib Korkmaz, K; Trivedi, P; Inderson, A; van Hoek, B; Rodriguez Girondo, M; Maljaars, J
Abstract: Background: Primary sclerosing cholangitis (PSC) is a chronic inflammation of the bile ducts leading to fibrosis and eventually cirrhosis. Aetiology of PSC remains unknown and no specific treatment can delay or arrest the progressive course of the disease with orthotopic liver transplantation (OLT) remaining the only curative option. Nonetheless, recurrent primary sclerosing cholangitis (rPSC) can occur after liver transplantation (rPSC) with considerable morbidity often leading to retransplantation. In the past decade large cohorts of patients with PSC undergoing OLT were analysed to identify risk factors for rPSC. The current systematic review and meta-analysis was conducted to summarise all available data to define risk factors for rPSC. Methods: The search of the following databases was performed: PubMed, Embase, Web of Science, Cochrane library for articles published until March 2018 using the medical subject headings sclerosing cholangitis, recurrence, liver transplantation, risk and risk factors. Studies addressing risk factors for developing rPSC after liver transplantation were eligible for inclusion in the review. Studies able to provide data to calculate hazard ratios (HR) and 95% confidence intervals (95% CI) were included in the meta-analysis. Quality of included studies was independently evaluated by two authors with the Newcastle Ottawa Scale (NOS) for cohort studies. Statistical analysis was performed using Cochrane Review Manager. Results: The electronic database search yielded 449 results. Sixteen retrospective cohort studies met the inclusion criteria for the review. Twelve studies were included for meta-analysis. Studies scored a median of 8 points (6–9) on the NOS. After excluding possibly overlapping cohorts we analysed recurrence a total cohort of 1899 patients, with median age ranging from 31 to 49 years, 1330 were male (70.0%) and 321 developed rPSC (16.9%). We found that colectomy before OLT, HR 0.63 (95% CI: 0.41–0.99), presence of cholangiocarcinoma (CCA) before OLT, HR 2.81 (95% CI: 1.34–5.87), presence of inflammatory bowel disease (IBD), HR 1.76 (95% CI: 1.19–2.61), donor age, HR 1.02 (95% CI 1.01–1.04), MELD score per point, HR 1.05 (95% CI: 1.02–1.08) and development of acute cellular rejection (ACR), HR 2.37 (95% CI: 1.30 – 4.32) were associated with the risk of rPSC. Conclusions: IBD presence, CCA before transplantation, donor age, MELD score and development of ACR were risk factors for recPSC. Performing a colectomy before liver transplantation was protective for rPSC.